2019
DOI: 10.34250/jkccn.2019.12.1.36
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors Related to Early Readmission to the Intensive Care Unit

Abstract: The purpose of this study was to identify status and characteristics of patients who have been readmitted to ICU, and to analyze risk factors associated with the readmission to ICU within 48hours. Method: Data were collected from patient's electronic medical reports from one hospital in B city. Participants were 2,937 patients aged 18 years old or older admitted to the ICU. Data were analyzed using odd ratios (ORs) from multivariate logistic regressions. Results: 2.2% of the 2,937 patients were early readmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Globally, ICU readmission are estimated to range from 2% to 25%,[ 14 , 15 ] and is undoubtedly associated with poor outcomes. [ 6 , 7 , 10 ] Hence, the readmission rate within 48 hours has been utilized as a KPI that reflects the quality of care provided by the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, ICU readmission are estimated to range from 2% to 25%,[ 14 , 15 ] and is undoubtedly associated with poor outcomes. [ 6 , 7 , 10 ] Hence, the readmission rate within 48 hours has been utilized as a KPI that reflects the quality of care provided by the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that older age, male gender, ICU admission diagnosis, admission source, and the Acute Physiology and Chronic Health Evaluation (APACHE) score are related to unplanned ICU readmission (Jang et al, 2019; Liu et al, 2017; Kang, 2016; Ohnuma et al, 2018). In addition, continuous renal replacement therapy (CRRT), mechanical ventilation, time of ICU discharge, length of ICU stay, and presence of tracheostomy are also associated with ICU readmission (Jeong et al, 2019; Jo et al, 2015; Ohnuma et al, 2018; Ponzoni et al, 2017).…”
mentioning
confidence: 99%
“…Moreover, the main risk factors known to date have been mostly identified in Western studies, and there is no validated scoring system to predict readmission after ICU discharge (Desautels et al, 2017; Pedersen, Meyer, & Uhrenfeldt, 2017). The aforementioned studies suggest that the risk factors vary depending on the time elapsed between ICU discharge and readmission (Desautels et al, 2017; Jang et al, 2019; Lin et al, 2018). One potential explanation for this finding is the variability in the causes and timing of readmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation